Analysis Of Factors Affecting Indonesia's Cinnamon Export Volume - Nainggolan, Saidin; Effran, Endy; Putri Yatma, Pino (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study aims to analyze the development of Indonesia’s cinnamon export volume and identify the factors affecting its export performance in the international market. The variables examined include Indonesia’s cinnamon export volume, domestic cinnamon production, China’s cinnamon production, Indonesia’s cinnamon export price, and the exchange rate of the Indonesian rupiah against the US dollar. The analysis employed the Autoregressive Distributed Lag (ARDL) approach to examine long-run relationships and the Error Correction Model (ECM) to identify short-run dynamics. The results indicate that Indonesia’s cinnamon export volume fluctuated over time but showed an increasing trend in the long run. The Bounds Test confirmed the existence of cointegration among the variables. In the long run, the current export price, the exchange rate lagged by one period, and China’s cinnamon production lagged by one and two periods have a positive and significant effect on Indonesia’s cinnamon export volume. Conversely, the previous period’s export volume has a significant negative effect on the current export volume. Domestic cinnamon production was found to have no significant effect.The short-run ECM results reveal a significant adjustment mechanism toward long-run equilibrium. China’s cinnamon production lagged by one period, domestic production lagged by one period, and export volume lagged by two periods negatively and significantly affect current export volume, while the current exchange rate has a positive effect.